Two Principal Strategies in Improving the Efficeincy of Jurusprudence Texts and Sources: With the Focus on the Causes of Judgments and Their Application - Abdol Hossein Rezaei Rad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
According to its most famous definitions, jurisprudence is based on the science of expressing and deducing judgments on their reasons, and the sources of jurisprudence and the textbooks of this field of humanities have not left any effort in expressing religious judgments and their reasons, but have proven experience. Due to the fact that the rulings are applicable in a variety of social and historical conditions, it is feasible and viable. Reasons alone are not enough, and the reason for the sentences and method of its implementation is significant, but unfortunately in the jurisprudential works, especially the Shiite jurisprudential works which include being afraid of divorce from divine commandments and falling into the trap of analogy and tastes, little has been done on these two categories. This research tries to increase the efficiency of the sources of jurisprudence and the strategies of the studies in this field and the need to address these two categories and the consequences of neglecting them in the sources and texts of jurisprudence. The present paper makes an attempt, through examples and actual examples as two important strategies, to increase the efficiency and outcome of jurisprudential texts and, at the same time, to highlight the damage of extremes in the methodology and causality of sentences.